At the Crossroads of Law and Ideology: The Ideology of Law as a Reflection of Social Ontology? - Platsas, Antonios E. (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The paper examines the link between ideology in law and social ontology. Whereas academic enquiries have thus far mainly concentrated on the link between law per se and social reality, the question of the relationship of the ideology of law and social ontology is by and large an academic terra incognita. The paper proceeds by examining a number of matters in furtherance of its analytical goals. Accordingly, there are three (3) lines of enquiry in the paper’s analysis: first, the author proceeds with the question as to whether ideology ought to inform legal doctrine in the first place. Should law be free from ideology? Can law be wholly free from ideology? Do the positivist credentials of much of modern law, e.g. in the context of liberal political theory, create a de facto ideology for our law? Is it not true that the very notion of constitutionalism also creates a sui generis ideology for our law? Is law just another way of transforming predominant ideology and collective practices into norms? Effectively, can there be law which is wholly disconnected from leading or predominant economic theory? In other words, are jurists expected to show compliance with economic theory inter aliaor should law be more of a Kelsenian island of epistemic purity, devoid of ideology, sociology and the like? Secondly, more importantly, iflaw ought to be characterised by a certain limited degree of ideology, should that ideology be driven by the social? Thus, if law should not be free from ideology, should the ideology, which characterises it, at any rate and at any point, reflect the ontologically social? If so, is that reflection just another way of promoting democracy? Naturally, whilst democracy is an ideal, it often becomes burdensome as to what the precise definition of democracy is or ought to be. So too, it becomes necessary to ensure that democracy, in its practical manifestation, does not hinder the application of law as a means which enables. For instance, the constitutional crises between 2012-2015, in significant parts of Europe, alert us to the fact that the socially ontological might not always lead to ideal results e.g. when it comes to respecting the established notion of the Rule of Law in the European legal sphere or, more widely, in Western legal space. Thirdly, what ought to be the social ontology’s input in the ideology of law? Whereas recognition is given to the democratic credentials of modern social ontology in many jurisdictions these days, it goes without saying that democracy ought not to deteriorate into populist understandings of the social. This being the case, it is also understood that there can be no one meaning or interpretation of social ontology throughout systems and regions or, indeed, any universal understandings thereof. What might be an ideal for the social ontology of the French Republic might not necessarily be an ideal for the social ontology of the State of Texas. Thus, the meaning of ‘ideal’ is rather relative in social ontological terms and cannot be and should not be the same from jurisdiction to jurisdiction. Nonetheless, this differentiation of the social ontology between different jurisdictional spaces is one which does not automatically provide moral legitimacy to electorates and legislatures around the world, when it comes to them infiltrating domestic law with their own social ideology, especially when such ideology is devoid of value and essence. Thus, the ontologically social is not a synonym to the ontologically abusive, in case social ideology informs the law.
Keywords: ideologia; prawo; ontologia społeczna